Solid-state battery and preparation method thereof

By forming uniformly arranged protrusions and depressions on the electrode and electrolyte surfaces of all-solid-state batteries, the problem of unstable interface contact in all-solid-state batteries is solved, achieving efficient interface bonding and improved battery performance, simplifying the manufacturing process and reducing costs.

CN121123364APending Publication Date: 2025-12-12CHERY AUTOMOBILE CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511318077.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

The interfacial contact problems between the electrodes and electrolytes in existing all-solid-state batteries include insufficient interfacial adhesion strength and excessively high interfacial impedance, resulting in poor electrochemical performance and cycle stability of the battery. Furthermore, existing processes pose risks of introducing foreign matter and challenges in large-scale production.

Method used

Laser processing is used to form uniformly arranged protrusions and depressions on the surfaces of the positive electrode, negative electrode, and all-solid electrolyte membrane. A sandwich-style stacked structure is used to form stacked units, and stable interface interlocking is achieved through hot pressing and isostatic pressing processes, ensuring the controllability and consistency of the interface contact area.

Benefits of technology

It significantly enhances interfacial bonding strength, reduces interfacial impedance, improves battery production yield and performance consistency, simplifies the production process, reduces costs and quality deviations, and improves battery stability and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121123364A_ABST
    Figure CN121123364A_ABST
Patent Text Reader

Abstract

The invention provides a solid-state battery and a preparation method thereof, and particularly relates to the technical field of solid-state batteries. The solid-state battery is composed of a plurality of laminated units, the laminated unit comprises a positive pole piece, an all-solid-state electrolyte membrane and a negative pole piece which are sequentially stacked according to a sandwich structure; among the positive pole piece, the all-solid-state electrolyte membrane and the negative pole piece, convex structures and concave structures which are uniformly arranged are distributed on any two mutually contacted surfaces of the positive pole piece, the all-solid-state electrolyte membrane and the negative pole piece. When the components of the solid-state battery are overlapped, the convex structures and the concave structures on the surfaces of the solid-state battery can be mutually engaged to form a stable micro-embedded structure, the interface bonding strength between the positive electrode and the electrolyte and between the negative electrode and the electrolyte is greatly enhanced through physical embedding, and the problem of unstable bonding in the prior art is solved. Meanwhile, the uniform concave-convex structure ensures the controllability and consistency of the interface contact area, effectively reduces and stabilizes the interface impedance, improves the performance consistency of the pole piece, and further improves the production yield and the overall performance stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, and in particular to a solid-state battery and its preparation method. Background Technology

[0002] With the rapid development of the lithium-ion battery industry and the continuous improvement of people's living standards, the market has placed higher demands on the performance of lithium-ion batteries. High safety, high energy density, high power characteristics, and wide temperature range adaptability have become the core development directions for high-performance lithium-ion batteries. However, traditional liquid lithium batteries, due to the use of liquid electrolytes, have inherent safety hazards. Risks such as short circuits, overheating, spontaneous combustion, and even explosions are difficult to completely avoid, which greatly limits their application in high-end fields.

[0003] Against this backdrop, all-solid-state batteries, employing solid-state electrolytes, have effectively solved the safety issues associated with liquid electrolytes due to their unique structural advantages, thus attracting widespread attention from the global scientific and industrial communities. However, the commercialization of all-solid-state batteries still faces a key bottleneck—the interfacial contact problem between the electrodes and the electrolyte. Insufficient interfacial adhesion strength and excessively high interfacial impedance directly affect the electrochemical performance and cycle stability of the battery. Therefore, how to improve the interfacial contact effect through optimizing interfacial treatment technology has become one of the core research topics in current all-solid-state battery research.

[0004] Currently, existing publicly available methods for adjusting the surface roughness of solid-state positive electrode sheets, negative electrode sheets, and electrolytes generally suffer from insufficient processing precision. They fail to achieve refined, microscopic, and customized surface control, resulting in poor adhesion stability at the positive electrode-electrolyte and negative electrode-electrolyte interfaces, large fluctuations in interface impedance, and difficulty in meeting the consistency requirements of battery performance. Meanwhile, mainstream surface treatment processes such as sandblasting, grinding, rolling, and coating all have significant drawbacks: sandblasting and grinding inevitably introduce foreign matter during the process, posing a potential threat to the battery's electrochemical performance and safety; rolling and coating processes, due to their high technical complexity and difficulty in process control, are difficult to deploy in large-scale production and cannot achieve the required precision standards for interface treatment. Furthermore, the poor consistency in adhesion strength and interface impedance of electrodes treated by these processes further reduces their feasibility for application in actual production lines.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a solid-state battery and a method for preparing the same, aiming to solve at least one of the above-mentioned technical problems in the prior art.

[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: The first aspect of the present invention provides a solid-state battery comprising a plurality of stacked units; the stacked unit includes a positive electrode, an all-solid electrolyte membrane and a negative electrode stacked sequentially in a sandwich structure; wherein any two of the positive electrode, the all-solid electrolyte membrane and the negative electrode have uniformly arranged protrusions and depressions distributed on any two surfaces that are in contact with each other.

[0008] In one embodiment of the present invention, the positive electrode sheet has uniformly arranged protrusions and depressions distributed on at least one side surface; the height difference between the protrusions and the depressions is 0.05~100μm.

[0009] In one embodiment of the present invention, the negative electrode sheet has uniformly arranged protrusions and depressions distributed on at least one side surface; the height difference between the protrusions and the depressions is 0.05~100μm.

[0010] In one embodiment of the present invention, the all-solid electrolyte membrane has uniformly arranged protrusions and depressions distributed on at least one side of its surface; the height difference between the protrusions and the depressions is 0.05~20μm.

[0011] Furthermore, the protruding structure includes a protruding point-shaped structure.

[0012] Preferably, the dot-like structure includes circular or square shapes.

[0013] Preferably, when the dot-like structure is circular, the diameter is 1~100μm, more preferably 10~50μm.

[0014] Preferably, when the electrical assembly structure is square, the side length is 1~100μm, more preferably 10~50μm.

[0015] Preferably, the spacing between the dotted structures is 1~100μm, and more preferably 10~50μm.

[0016] In one embodiment of the present invention, the protruding structure or the recessed structure is formed by laser processing.

[0017] Preferably, the pulse width of the laser is selected from at least one of femtosecond, picosecond, and nanosecond.

[0018] Preferably, the power of the laser is 1~1000W.

[0019] Preferably, the frequency of the laser is 1~5000KHz.

[0020] The second aspect of the present invention provides a method for preparing the solid-state battery, comprising selecting at least two of a positive electrode, a negative electrode, or an all-solid electrolyte membrane, and forming uniformly arranged protrusion and depression structures on their mutually contacting surfaces; then forming a stacked unit by sandwiching the positive electrode, the all-solid electrolyte membrane, and the negative electrode; and stacking a plurality of the stacked units alternately according to polarity to form the solid-state battery.

[0021] Further, the preparation method includes the following steps: A. Forming patterns on both sides of the positive electrode and the negative electrode respectively; the patterns are composed of uniformly arranged raised and recessed structures; B. Forming a pattern on the first surface of the all-solid electrolyte membrane; C. Adhering the patterned negative electrode to the first surface on both sides respectively, with the unpatterned second surface located on the outermost side, and then forming a pattern on the second surface to obtain a composite negative electrode; D. Then stacking the patterned positive electrode and the composite negative electrode to obtain a stacked unit, and stacking several stacked units alternately according to polarity to form the solid-state battery.

[0022] Furthermore, in step C, the bonding method includes transfer printing.

[0023] Furthermore, the preparation method also includes hot pressing and isostatic pressing processes after alternating stacking.

[0024] Compared with the prior art, the present invention has at least the following beneficial effects: The solid-state battery provided by this invention allows the raised and recessed structures on the surface to interlock during contact when the components are stacked, forming a stable micro-embedded structure. This physical interlocking significantly enhances the interfacial adhesion strength between the positive electrode and electrolyte, and between the negative electrode and electrolyte, effectively improving the problem of unstable interfacial adhesion in traditional technologies. At the same time, the uniformly distributed raised and recessed structure ensures the controllability and consistency of the interfacial contact area, avoiding the problem of large fluctuations in interfacial impedance caused by uneven contact, and significantly reducing interfacial impedance. In addition, the preset uniform raised and recessed structure enables refined interface processing, improving the consistency of electrode adhesion strength and impedance performance, thereby improving the yield rate of battery production and the overall performance consistency of the product.

[0025] The preparation method provided by this invention has high process compatibility, eliminating the need for complex processes such as sandblasting and grinding that easily introduce foreign matter, and avoiding the difficulties of large-scale deployment of rolling and coating processes. It can be adapted to upgrade existing production systems to reduce production line iteration costs. By pre-forming a uniform and controllable uneven structure, it replaces traditional fine processing methods, simplifies the process, reduces quality deviations caused by process fluctuations, and improves production controllability and efficiency. At the same time, the uniform structural design ensures the consistency of component interface treatment effects and key performance parameters in mass production, reducing defect rates and production losses. Furthermore, the uneven structure parameters can be adjusted to meet different battery performance requirements, resulting in high process flexibility. Attached Figure Description

[0026] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0027] Figure 1 This is a front view of the structure of each component of a solid-state battery; Figure 2 Different patterns are formed by raised and recessed structures; Figure 3 This is a side view of the components of the solid-state battery provided by the present invention.

[0028] Icons: 1-Positive electrode; 11-First surface of positive electrode; 12-Second surface of positive electrode; 2-Negative electrode; 21-First surface of negative electrode; 22-Second surface of negative electrode; 3-All-solid-state electrolyte membrane; 31-First surface of all-solid-state electrolyte membrane; 32-Second surface of all-solid-state electrolyte membrane; 4-Composite negative electrode; 41-First surface of composite negative electrode; 42-Second surface of composite negative electrode; 51-First pattern; 52-Second pattern; 53-Third pattern; 54-Fourth pattern. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0030] In the following, the terms “comprising,” “having,” and their cognates, which may be used in various embodiments of the invention, are intended only to indicate a particular feature, number, step, operation, element, component, or combination thereof, and should not be construed as excluding, firstly, the presence of one or more other features, numbers, steps, operations, elements, components, or combinations thereof, or adding the possibility of one or more features, numbers, steps, operations, elements, components, or combinations thereof.

[0031] In this invention, such as Figure 1 As shown, the positive electrode 1 consists of three parts: a positive electrode tab for current conduction, a positive electrode coating layer with attached positive active material, and a positive current collector for support and conductivity. The negative electrode 2 also consists of three parts: a negative electrode tab for current conduction, a negative electrode coating layer with attached negative active material, and a negative current collector for support and conductivity. The all-solid-state electrolyte membrane 3 consists of two parts: an electrolyte membrane that performs ion conduction, and a base film used to support the electrolyte membrane before the transfer printing process.

[0032] The first aspect of the present invention provides a solid-state battery composed of a plurality of stacked units; the stacked unit includes a positive electrode 1, an all-solid electrolyte membrane 3 and a negative electrode 2 stacked sequentially in a sandwich structure; among the three, any two surfaces of the positive electrode 1, the all-solid electrolyte membrane 3 and the negative electrode 2 are provided with uniformly arranged protrusions and depressions.

[0033] The solid-state battery provided by this invention allows the raised and recessed structures on the surface to interlock during contact when the components are stacked, forming a stable micro-embedded structure. This physical interlocking significantly enhances the interfacial adhesion strength between the positive electrode and electrolyte, and between the negative electrode and electrolyte, effectively improving the problem of unstable interfacial adhesion in traditional technologies. At the same time, the uniformly distributed raised and recessed structure ensures the controllability and consistency of the interfacial contact area, avoiding the problem of large fluctuations in interfacial impedance caused by uneven contact, and significantly reducing interfacial impedance. In addition, the preset uniform raised and recessed structure enables refined interface processing, improving the consistency of electrode adhesion strength and impedance performance, thereby improving the yield rate of battery production and the overall performance consistency of the product.

[0034] This solid-state battery is composed of multiple identical stacked units, achieving large-scale output of battery performance through the repeated stacking of units. Each stacked unit adopts a "sandwich" core stacked structure, specifically arranged as follows: positive electrode 1, all-solid electrolyte membrane 3, and negative electrode 2. Among them, the all-solid electrolyte membrane 3 is located in the middle, undertaking the key function of ion conduction between the positive and negative electrodes, ensuring the smooth progress of electrochemical reactions inside the battery; on the other hand, it also plays a role in physically isolating the positive and negative electrodes, effectively avoiding the risk of short circuits.

[0035] In one embodiment of the present invention, the positive electrode 1 has uniformly arranged protrusions and depressions distributed on at least one side surface; the height difference between the protrusions and the depressions is 0.05~100μm.

[0036] The positive electrode 1 has a sheet-like structure and typically has two opposing main surfaces (i.e., the two surfaces with the largest areas), namely the first surface 11 of the positive electrode and the second surface 12 of the positive electrode opposite to the first surface 11. In a specific embodiment of the present invention, uniformly arranged protrusions and depressions can be formed on the first surface 11 and / or the second surface 12 of the positive electrode to increase the surface area of ​​the positive electrode 1 in contact with other components.

[0037] Typically, but not limitingly, the height difference between the protrusion and the recess formed on the positive electrode 1 can be, for example, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 80 μm or 100 μm, or any value in the range of 0.05 to 100 μm.

[0038] In one embodiment of the present invention, the negative electrode 2 has uniformly arranged protrusions and depressions distributed on at least one side of its surface; the height difference between the protrusions and the depressions is 0.05~100μm.

[0039] Typically, but not limitingly, the height difference between the protrusion and the recess formed on the negative electrode 2 can be, for example, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 80 μm or 100 μm, or any value in the range of 0.05 to 100 μm.

[0040] In either the positive electrode 1 or the negative electrode 2, the height difference between the protruding structure and the recessed structure is less than 0.05 μm. This indicates that the morphological difference between the protrusion and the recess is too small, making it difficult to form an effective physical fit to improve interface contact. Furthermore, this results in high processing control difficulty and a high risk of failure due to subsequent processing. If the height difference exceeds 100 μm, excessively large protrusions may push against the all-solid electrolyte membrane 3, causing it to rupture or trigger a short circuit. Excessively deep recesses may cause uneven electrode thickness, forming "dead volume" and reducing the utilization rate of active materials. They may also accelerate electrode aging due to stress concentration. The 0.05~100 μm range is suitable for the conventional thickness characteristics of the electrode and the electrolyte membrane. This not only reduces interface voids and improves ion conduction efficiency through effective fit but can also be stably achieved using existing precision processing technology, thus balancing performance requirements and mass production feasibility.

[0041] In one embodiment of the present invention, the all-solid electrolyte membrane 3 has uniformly arranged protrusions and depressions distributed on at least one side of its surface; the height difference between the protrusions and the depressions is 0.05~20μm.

[0042] Typically, but not limitingly, the height difference between the protrusions and the recesses formed on the all-solid electrolyte membrane 3 can be, for example, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, or any value in the range of 0.05 to 20 μm.

[0043] The typical thickness of all-solid-state electrolyte membranes (3) is 10-50 μm. If the height difference between the protrusions and depressions exceeds 20 μm, the proportion of the membrane thickness will increase significantly. The protrusions are prone to localized stress concentration during assembly, bonding, or slight volume changes during battery charging and discharging, leading to membrane rupture or microcracks. This directly damages the ion conduction pathway and insulation performance, and may even cause short circuits between the positive and negative electrodes. From an interface and performance perspective, excessively high protrusions will form a "rigid support" with adjacent electrodes, which will disrupt the interface that originally needed to be tightly bonded and increase the area of ​​virtual contact. At the same time, excessively deep depressions will create localized "thickness gaps" on the surface of the electrolyte membrane, which may lead to longer ion conduction paths or conduction dead zones in the depressed areas, increasing interface impedance. In addition, the processing technology of all-solid-state electrolyte membranes (3) (such as micro-nano imprinting and precision coating) is more suitable for forming fine structures within 20 μm. Exceeding this range will not only increase the processing difficulty and cost, but also make it difficult to ensure the uniformity of the protrusions and depressions, ultimately affecting the stability and consistency of battery performance.

[0044] Furthermore, the protruding structure includes a protruding point-shaped structure.

[0045] Preferably, the dot structure includes a circle or a square. The shape of the dot structure is not limited. It can be a regular shape such as a circle or a square, or it can be a triangle, a polygon or other irregular shape according to actual design requirements (such as interface bonding effect, processing technology adaptability, etc.).

[0046] Preferably, when the dot-like structure is circular, the diameter is 1~100μm, more preferably 10~50μm.

[0047] Preferably, when the dotted structure is square, the side length is 1~100μm, more preferably 10~50μm.

[0048] Typically, but not limitingly, the diameter or side length can be, for example, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, or any value in the range of 1 to 100 μm; in a preferred embodiment, the diameter or length of the point structure can be, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, or any value in the range of 10 to 50 μm.

[0049] Preferably, the spacing between the dotted structures is 1~100μm, and more preferably 10~50μm.

[0050] Typically, but not limitingly, the spacing of the dot structures can be, for example, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, or any value in the range of 1 to 100 μm; in a preferred embodiment, the spacing of the dot structures can be, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, or any value in the range of 10 to 50 μm.

[0051] A spacing of 1–100 μm between the dots ensures uniform distribution and prevents dense stacking of protrusions due to insufficient spacing. If the spacing is less than 1 μm, adjacent protrusions are prone to mutual compression or morphological fusion during processing (such as imprinting or curing), which can damage the integrity of the concave-convex structure and prevent effective interlocking. Simultaneously, dense protrusions may create "local barriers" at the interface, affecting the uniform conduction of ions between the electrode and the electrolyte membrane. On the other hand, if the spacing is greater than 100 μm, the sparse distribution of protrusions leads to insufficient contact points between the electrolyte membrane and the electrode. The design goal of reducing interfacial voids through the dot structure fails, and the interface is prone to generating numerous tiny voids due to incomplete contact, thereby increasing interfacial impedance and reducing the battery's ion conduction efficiency. Furthermore, sparse protrusions cannot provide uniform support for the electrolyte membrane, making the membrane more susceptible to local deformation or damage due to uneven stress during battery assembly or charging / discharging.

[0052] In one embodiment of the present invention, the protruding structure or the recessed structure is formed by laser processing. Based on a preset structural design (such as the size, shape, and depth of the protrusion / recess), the processing effect is achieved by adjusting parameters such as laser power, scanning path, and action time. The advantages of this process are that it can precisely control the dimensional accuracy and uniformity of the structure, avoiding structural damage that may occur with traditional machining. Furthermore, the processing is easily adaptable to automated production lines, enabling stable batch production of micro / nano-scale protruding and concave structures that meet design requirements, thereby ensuring the consistency of the interface contact between the all-solid-state electrolyte membrane 3 and the electrode, as well as the battery performance.

[0053] Preferably, the pulse width of the laser is selected from at least one of femtosecond, picosecond, and nanosecond.

[0054] Preferably, the power of the laser is 1~1000W.

[0055] Typically, but not limitingly, the power of the laser can be, for example, 1 W, 10 W, 50 W, 100 W, 200 W, 300 W, 400 W, 500 W, 600 W, 700 W, 800 W, 900 W or 1000 W, or any value in the range of 1 to 1000 W.

[0056] Preferably, the frequency of the laser is 1~5000KHz.

[0057] Typically, but not limitingly, the frequency of the laser can be, for example, 1 kHz, 10 kHz, 50 kHz, 100 kHz, 500 kHz, 1000 kHz, 1500 kHz, 2000 kHz, 2500 kHz, 3000 kHz, 3500 kHz, 4000 kHz, 4500 kHz, or 5000 kHz, or any value in the range of 1 to 5000 kHz.

[0058] The second aspect of the present invention provides a method for preparing the solid-state battery, wherein at least two of the following are selected: a positive electrode 1, a negative electrode 2, or an all-solid electrolyte membrane 3, and a uniformly arranged protruding structure and a recessed structure are formed on their mutually contacting surfaces; then, a stacked unit is formed by sandwich-like stacking of the positive electrode 1, the all-solid electrolyte membrane 3, and the negative electrode 2; and a plurality of the stacked units are stacked alternately according to polarity to form the solid-state battery.

[0059] The preparation method provided by this invention has high process compatibility, eliminating the need for complex processes such as sandblasting and grinding that easily introduce foreign matter, and avoiding the difficulties of large-scale deployment of rolling and coating processes. It can be adapted to upgrade existing production systems to reduce production line iteration costs. By pre-forming a uniform and controllable uneven structure, it replaces traditional fine processing methods, simplifies the process, reduces quality deviations caused by process fluctuations, and improves production controllability and efficiency. At the same time, the uniform structural design ensures the consistency of component interface treatment effects and key performance parameters in mass production, reducing defect rates and production losses. Furthermore, the uneven structure parameters can be adjusted to meet different battery performance requirements, resulting in high process flexibility.

[0060] Further, the preparation method includes the following steps: A. Forming patterns on both sides of the positive electrode 1 and the negative electrode 2 respectively; the patterns are composed of uniformly arranged raised and recessed structures; B. Forming a pattern on the first surface 31 of the all-solid electrolyte membrane; C. Adhering the patterned negative electrode 2 to the first surface on both sides respectively, with the unpatterned second surface located on the outermost side, and then forming a pattern on the second surface to obtain a composite negative electrode 4; D. Then stacking the patterned positive electrode 1 and the composite negative electrode 4 to obtain a stacked unit, and stacking several stacked units alternately according to polarity to form the solid-state battery.

[0061] It should be noted that for the two interfaces that are ultimately bonded together during the solid-state battery assembly process (i.e., the contact surface between the positive electrode 1 and the all-solid-state electrolyte membrane 3, and the contact surface between the all-solid-state electrolyte membrane 3 and the negative electrode 2), it is recommended that the raised and recessed structures on these two bonding surfaces be matched and consistent. This design can promote precise fitting of the raised and recessed structures on both sides of the interface, thereby forming a tighter interface bonding structure.

[0062] Matching does not require identical surface structures, but rather emphasizes that the protrusions and recesses on the two contact surfaces must match each other in three aspects: In terms of position, the center points of the protrusions and recesses must precisely correspond to avoid misalignment; in terms of shape, they must be consistent (e.g., a circular protrusion corresponds to a circular recess, a strip-shaped protrusion corresponds to a strip-shaped recess); and in terms of size, the height of the protrusion matches the depth of the recess, and the width of the protrusion matches the inner diameter of the recess, reducing the gap between them. By matching patterns to form a tight "protrusion-embedded-recess" structure, on the one hand, air gaps and virtual contact areas on the contact surfaces are significantly reduced, lowering the interfacial ion conduction resistance; on the other hand, the physical bonding strength between components is enhanced, alleviating the interface separation problem caused by slight volume changes during battery charging and discharging, thereby improving battery stability and cycle life.

[0063] In some embodiments of the present invention, the different patterns formed by the raised structures and the recessed structures are as follows: Figure 2 As shown, 51 is an example of the first pattern 51 formed, 52 is an example of the second pattern 52 formed, 53 is an example of the third pattern 53 formed, and 54 is an example of the fourth pattern 54 formed.

[0064] Further, in step C, the bonding method includes transfer printing. Both the first surface 21 and the second surface 22 of the negative electrode sheet have patterns, which are bonded and transferred to the first surface 31 (patterned surface of the all-solid electrolyte membrane 3) of the all-solid electrolyte membrane. Through a transfer printing process (such as hot pressing transfer printing, UV curing transfer printing, etc.), the first surface 31 of the all-solid electrolyte membrane is bonded to both sides of the negative electrode sheet 2, and the second surface 32 (non-patterned surface of the all-solid electrolyte membrane 3) is exposed on the outermost side.

[0065] Furthermore, the preparation method also includes hot pressing and isostatic pressing processes after alternating stacking. Hot pressing, through heating and directional pressure, pushes the layers together by compression, eliminating macroscopic voids at the interface and establishing initial contact. Simultaneously, it softens and solidifies the material to achieve structural shaping of the stack, and also compresses the internal pores of the electrode to improve density. Isostatic pressing, with uniform pressure in all directions (usually higher than hot pressing), further eliminates microscopic dead-angle voids at the interface, achieving seamless bonding and avoiding material damage caused by uneven local stress. This ensures a uniform and dense overall structure while strengthening interlayer bonding to improve cycle stability. The combination of these two processes avoids the shortcomings of a single process—hot pressing lays the foundation for shaping and macroscopic bonding in isostatic pressing, while isostatic pressing compensates for the insufficient microscopic bonding and uniformity of hot pressing, ultimately helping the battery achieve its performance goals of low impedance, high capacity, long cycle life, and high safety.

[0066] The present invention is further illustrated below with specific embodiments and comparative examples. However, it should be understood that these embodiments are merely for illustrative purposes and should not be construed as limiting the invention in any way. Unless otherwise specified, the raw materials used in the embodiments and comparative examples of the present invention were carried out under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.

[0067] The components of the embodiments and comparative examples are configured as follows: Positive electrode 1: The current collector is a 12μm aluminum foil; the active material layer is formed by coating a mixture of lithium iron phosphate (LFP), carbon black (Super P), and polyvinylidene fluoride (PVDF) in a mass ratio of 94:3:3, and the thickness of the active material layer is 100μm.

[0068] Negative electrode 2: The current collector is a 6μm copper foil; the active material layer is formed by coating graphite, carbon black, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 95:2:1.5:1.5; the thickness of the active material layer is 80μm.

[0069] All-solid-state electrolyte membrane 3: made of Li7P3S 11 A film with a thickness of 70 μm was formed.

[0070] Example 1 This embodiment provides a solid-state battery, such as Figure 3 The specific steps shown are as follows: 1. Uniformly distributed protrusions and depressions are formed on the first surface 11 and the second surface 12 of the positive electrode using laser processing. The laser is a picosecond laser with a pulse width of 10 ps, ​​an output power of 300 W, a scanning frequency of 2000 kHz, a scanning speed of 500 mm / s, a laser wavelength of 1064 nm, and a focused spot diameter of 20 μm. The laser energy density is controlled between 1.5 and 3.0 J / cm². 2 Within the range, and using a layer-by-layer scanning strategy, the microstructure of the positive electrode 1 surface is precisely processed, thereby forming a periodically arranged protrusion and depression structure with a height difference of 50μm on the surface. The protrusion structure is a circular dot structure with a diameter of 30μm and the center distance between adjacent protrusion points is 40μm.

[0071] 2. Uniformly distributed protrusions and depressions are formed on the first surface 21 and the second surface 22 of the negative electrode using laser processing. The laser parameters and pattern are the same as those of the positive electrode 1.

[0072] 3. A uniformly distributed protrusion and depression structure is formed on the first surface 31 of the all-solid-state electrolyte membrane using laser processing. This structure is formed by femtosecond laser processing with the following laser parameters: pulse width 50 fs, power 100 W, frequency 2000 kHz, scanning speed 500 mm / s, laser wavelength 1064 nm, and focused spot diameter 20 μm. This results in a periodically arranged protrusion and depression structure with a height difference of 10 μm on the surface. The protrusion structure is a circular dot structure with a diameter of 30 μm, and the center-to-center distance between adjacent protrusions is 40 μm.

[0073] 4. Transfer and bond the first surface 21 of the negative electrode sheet to the first surface 31 of the all-solid electrolyte membrane, and transfer and bond the second surface 22 of the negative electrode sheet to the first surface 31 of another all-solid electrolyte membrane, with the second surface 32 of the all-solid electrolyte membrane exposed on the outermost side. Form a pattern according to the laser parameters and structural parameters in step 3 to obtain the composite negative electrode sheet 4. The first surface 41 of the composite negative electrode sheet is the second surface 32 of the all-solid electrolyte membrane, and the second surface 42 of the composite negative electrode sheet is the second surface 32 of another all-solid electrolyte membrane.

[0074] 5. Stack the patterned positive electrode 1 and the composite negative electrode 4 obtained in step 1 to form a single stacked unit; stack 15 stacked units in an alternating positive and negative electrode manner to form a battery stack; perform hot pressing and isostatic pressing on the stacked battery to obtain a solid-state battery.

[0075] Example 2 This embodiment provides a solid-state battery. Unlike embodiment 1, patterns are processed on both sides of the all-solid electrolyte membrane 3, and patterns are processed on the side of the positive electrode 1 closest to the all-solid electrolyte membrane 3, and patterns are processed on the side of the negative electrode 2 closest to the all-solid electrolyte membrane 3. The other steps are the same as in embodiment 1, and will not be repeated here.

[0076] Example 3 This embodiment provides a solid-state battery. Unlike embodiment 1, a pattern is processed on the side of the all-solid electrolyte membrane 3 near the positive electrode 1, and a pattern is also processed on the side of the positive electrode 1 near the all-solid electrolyte membrane 3. No pattern is processed on the negative electrode 2, and no pattern is processed on the other side of the positive electrode 1 and the other side of the all-solid electrolyte membrane 3. All other steps are the same as in embodiment 1, and will not be repeated here.

[0077] Example 4 This embodiment provides a solid-state battery. Unlike embodiment 1, a pattern is processed on the side of the all-solid electrolyte membrane 3 near the negative electrode 2, and a pattern is also processed on the side of the negative electrode 2 near the all-solid electrolyte membrane 3. No pattern is processed on the positive electrode 1, and no pattern is processed on the other side of the negative electrode 2 and the other side of the all-solid electrolyte membrane 3. All other steps are the same as in embodiment 1, and will not be repeated here.

[0078] Example 5 This embodiment provides a solid-state battery. Unlike embodiment 1, a patterned structure is formed on both sides of the all-solid electrolyte membrane 3 and the positive electrode 1, while no pattern is processed on the negative electrode 2. The other steps are the same as in embodiment 1, and will not be repeated here.

[0079] Example 6 This embodiment provides a solid-state battery. Unlike embodiment 1, a patterned structure is formed on both sides of the all-solid electrolyte membrane 3 and the negative electrode 2, while no pattern is processed on the positive electrode 1. The other steps are the same as in embodiment 1, and will not be repeated here.

[0080] Comparative Example 1 This comparative example provides a solid-state battery. A composite negative electrode 4 is obtained by transferring a fully solid electrolyte membrane 3 onto both sides of the negative electrode 2. Then, the positive electrode 1 and the composite negative electrode 4 are stacked to form a single stacked unit. Several stacked units are stacked in an alternating manner of positive and negative electrodes to form a battery stack. The stacked battery is subjected to hot pressing and isostatic pressing treatment to obtain a solid-state battery.

[0081] Comparative Example 2 This comparative example provides a solid-state battery. Unlike Example 1, a patterned structure is formed only on one side of the positive electrode 1. No patterns are processed on the other negative electrode 2 and the all-solid electrolyte membrane 3. The other steps are the same as in Example 1, and will not be described again here.

[0082] Comparative Example 3 This comparative example provides a solid-state battery. Unlike Example 1, patterned structures are formed only on both sides of the positive electrode 1. No patterns are processed on the other negative electrode 2 and the all-solid electrolyte membrane 3. The other steps are the same as in Example 1, and will not be described again here.

[0083] Comparative Example 4 This embodiment provides a solid-state battery. Unlike embodiment 1, a pattern structure is formed only on one side of the negative electrode 2. No patterns are processed on the other positive electrode 1 and the all-solid electrolyte membrane 3. The other steps are the same as in embodiment 1, and will not be described again here.

[0084] Comparative Example 5 This comparative example provides a solid-state battery. Unlike Example 1, patterned structures are formed only on both sides of the negative electrode 2. No patterns are processed on the other positive electrode 1 and the all-solid electrolyte membrane 3. The other steps are the same as in Example 1, and will not be repeated here.

[0085] Comparative Example 6 This comparative example provides a solid-state battery. Unlike Example 1, a patterned structure is formed only on one side of the all-solid electrolyte membrane 3. No patterns are processed on the other positive electrode 1 and negative electrode 2. The other steps are the same as in Example 1, and will not be described again here.

[0086] Comparative Example 7 This comparative example provides a solid-state battery. Unlike Example 1, patterned structures are formed only on both sides of the all-solid electrolyte membrane 3. No patterns are processed on the other positive electrode 1 and negative electrode 2. The other steps are the same as in Example 1, and will not be repeated here.

[0087] Comparative Example 8 This comparative example provides a solid-state battery. Unlike Example 1, a patterned structure is formed on both sides of the positive electrode 1 and the negative electrode 2. No pattern is processed on the all-solid electrolyte membrane 3. The other steps are the same as in Example 1, and will not be described again here.

[0088] Test case Electrochemical performance tests were performed on the solid-state batteries obtained in the examples and comparative examples.

[0089] The internal resistance was tested using an ACR testing device.

[0090] The electrochemical performance test procedure is as follows: At 45℃ and 20 MPa, charge at a constant current of 0.33C to 4.2V, then charge at a constant voltage to 100% SOC (cutoff current 0.05C). After resting for 600s, discharge at a constant current of 0.33C to 0% SOC (cutoff voltage 2.5V). After resting for 600s, cycle 100 times. Record the discharge capacity of the first cycle as C1 and the discharge capacity of the 100th cycle as C2. Calculate the capacity retention rate using the formula: Capacity retention rate = C2 / C1 × 100%.

[0091] The results are shown in Table 1 below.

[0092] Table 1

[0093] As can be seen from Table 1, by setting matching protrusion and depression structures on the contact surfaces of the positive electrode, negative electrode and all-solid electrolyte membrane in this invention, the interfacial adhesion strength can be significantly enhanced, the interfacial impedance can be reduced, and the cycle stability and capacity retention of the battery can be improved.

[0094] In Example 1, matching structures were provided at all contact interfaces, resulting in the best interface fitting effect and exhibiting the lowest internal resistance (89mΩ) and the highest capacity retention (89.5%). In contrast, Example 2 had unprocessed structures on one side of each of the positive and negative electrodes, which prevented some interfaces from forming effective fitting during the stacking process, leading to slightly lower performance than Example 1.

[0095] Furthermore, the intercalation effect of the negative electrode-electrolyte interface has a more significant impact on battery performance. For example, the performance of Example 4 (structure only on the negative electrode side) is better than that of Example 3 (structure only on the positive electrode side), indicating that optimizing the negative electrode interface is more beneficial to improving overall performance.

[0096] Furthermore, Comparative Examples 3, 5, and 8 show that if the structure is only fabricated on the electrode but not matched and interlocked with the electrolyte membrane, the interface improvement effect is limited, and the performance improvement is not significant. Comparative Examples 6 and 7 further illustrate that if the structure is only fabricated on the electrolyte membrane but not matched with the electrode, the interface performance improvement effect is also limited, and may even have a negative impact due to the structure disrupting the flatness of the electrolyte membrane.

[0097] In summary, this invention achieves physical interlocking of the interface by designing matching protruding and recessed structures, which significantly improves the interfacial contact performance between the electrode and electrolyte membrane in solid-state batteries. It solves the problems of unstable interfacial adhesion and high interfacial impedance in traditional technologies, thereby improving the overall performance and stability of the battery.

[0098] Finally, it should be noted that the above-described embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and not to limit it. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the technical scope disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A solid-state battery, characterized in that, It consists of several stacked units; The stacked unit comprises a positive electrode sheet, an all-solid electrolyte membrane, and a negative electrode sheet stacked sequentially in a sandwich structure. Of the positive electrode, the all-solid electrolyte membrane, and the negative electrode, any two surfaces in contact with each other have uniformly arranged protruding and recessed structures.

2. The solid-state battery according to claim 1, characterized in that, The positive electrode sheet has uniformly arranged protrusions and depressions distributed on at least one side of its surface; The height difference between the protruding structure and the recessed structure is 0.05~100μm.

3. The solid-state battery according to claim 1, characterized in that, The negative electrode sheet has uniformly arranged protrusions and depressions distributed on at least one side of its surface; The height difference between the protruding structure and the recessed structure is 0.05~100μm.

4. The solid-state battery according to claim 1, characterized in that, The all-solid electrolyte membrane has uniformly arranged protrusions and depressions distributed on at least one side of its surface. Preferably, the height difference between the protruding structure and the recessed structure is 0.05~20μm.

5. The solid-state battery according to any one of claims 1 to 4, characterized in that, The protruding structure includes a protruding point-shaped structure; Preferably, the dot-like structure includes circles or squares; Preferably, when the dot-like structure is circular, the diameter is 1~100μm, more preferably 10~50μm; Preferably, when the dot-like structure is square, the side length is 1~100μm, more preferably 10~50μm; Preferably, the spacing between the dotted structures is 1~100μm, and more preferably 10~50μm.

6. The solid-state battery according to any one of claims 1 to 4, characterized in that, The protruding structure or the recessed structure is formed by laser processing; Preferably, the pulse width of the laser is selected from at least one of femtosecond, picosecond, and nanosecond. Preferably, the power of the laser is 1~1000W; Preferably, the frequency of the laser is 1~5000KHz.

7. A method for preparing a solid-state battery according to any one of claims 1 to 6, characterized in that, Select at least two of the following: positive electrode, negative electrode, or all-solid electrolyte membrane, and form a uniformly arranged protrusion and depression structure on their contacting surfaces. Then, a stacked unit is formed by sandwiching the positive electrode, the all-solid electrolyte membrane, and the negative electrode. The solid-state battery is formed by stacking several of the stacked units in alternating polarities.

8. The preparation method according to claim 7, characterized in that, Includes the following steps: A. Patterns are formed on both sides of the positive electrode and the negative electrode, respectively; the patterns are composed of uniformly arranged raised and recessed structures; B. Forming a pattern on the first surface of the all-solid electrolyte membrane; C. The patterned negative electrode sheet is attached to the first surface on both sides, with the unpatterned second surface located on the outermost side. Then, a pattern is formed on the second surface to obtain a composite negative electrode sheet. D. Then, the patterned positive electrode sheet is stacked with the composite negative electrode sheet to obtain a stacked unit, and several stacked units are stacked alternately according to polarity to form the solid-state battery.

9. The preparation method according to claim 8, characterized in that, In step C, the bonding method includes transfer printing.

10. The preparation method according to any one of claims 7 to 9, characterized in that, It also includes hot pressing and isostatic pressing processes after alternating stacking.

Citation Information

Cited By

  • Preparation method and preparation device of composite electrode structure of all-solid-state battery

    CN121439714A

  • Method and apparatus for preparing composite electrode structures for all-solid-state batteries

    CN121439714B